A gamification no ensino superior: projeto aplicado como incentivo na educação - Medeiros, Renato Alexandre de (2020)
A research has the general objective or study of a gamification project applied to higher education, using narration concepts. The process occurs through semantic exercise applications, conducted with students in the first and second period of a Digital Games course. Data collection will be performed through bibliographical research, academic papers and articles. One of the reasons for this proposal is the lack of research on the practical way to relate gamification actions with higher education. Today, research related to the topic of gamification, carried out by professionals in the area to serve students of elementary and high school. However, it found few studies that were conducted, having as object of study the students of higher education. Taking into account that these students go through the whole process of learning in higher education, where the engagement should be as intense as in the coming years. Students in this learning period should try the most active way and thus reach the most prepared and fit job market. In fact, studies with these objects of study are still limited. This research seeks to answer the following question: can gamification be an engaging tool for higher education? How can communicational productions generated from the concept of digital narratives bring more selected and musical elements? The methodology was based on a qualitative research through data collection instruments, interviews and records, and provides information on the registration of students who study during the research period. It took place from February to June and August to December 2019. Studies related to the subject also had problems with theses and dissertations. The theoretical references that support this research are the concepts of gamification, game development (NOVAK, 2010) and reality in game (MCGONIGAL, 2012; SCHELL, 2011). The context of this investigation involves spaces for research, teaching and extension of institutions where researchers and partners operate. The expected result of this research is the development of a gamified project for higher education, taking as reference the previous studies and the theoretical references addressed